Nursing care using roy’s adaptation model–based mirror therapy for physical mobility impairment in stroke patients: A case study - Saputra, Agusdiman; Susanti, Mira; Pratiwi, Siti Hardiyanti; KK, Indra Frana Jaya; Kastina, Kastina; Regina, Regina (Lentera Perawat, 2025)
Background: Stroke is a common neurological disorder that requires prompt and appropriate management to prevent functional impairment. Non-pharmacological nursing interventions play an important role in supporting motor recovery, one of which is Mirror Therapy, which facilitates motor relearning through visual feedback mechanisms. Objective: This study aimed to implement nursing care for stroke patients through the application of Mirror Therapy based on Roy’s Adaptation Model. Methods: A descriptive study with a case study approach was conducted involving three stroke patients at RSUD Siti Fatimah. The intervention consisted of Mirror Therapy exercises integrated with Roy’s Adaptation Model. Data collection techniques included nursing assessment, observation, physical examination, and documentation. Nursing diagnoses were established based on the Indonesian Nursing Diagnosis Standards (SDKI), and interventions were implemented using the Indonesian Nursing Intervention Standards (SIKI) and evaluated with the Indonesian Nursing Outcome Standards (SLKI). Results: Initial assessments of all three patients revealed complaints of unilateral extremity weakness and dizziness. The identified nursing diagnoses included impaired physical mobility and risk of ineffective cerebral perfusion. After three days of Mirror Therapy intervention, all patients demonstrated improvement in extremity muscle strength scores. These findings indicate a positive functional response to the intervention. Conclusion: Mirror Therapy based on Roy’s Adaptation Model is effective in improving extremity muscle strength and addressing impaired physical mobility in patients with non-hemorrhagic stroke. This intervention can be considered a valuable non-pharmacological nursing approach to support motor recovery in stroke patients.